Thrombosis warning in children suffering from Henoch-Schonlein Purpura - Luan Li; Jingwen Zhang; Yunying Zhang; Hong Ji (Wolters Kluwer Medknow Publications, 2013)
Henoch-Schonlein Purpura (HSP) is one of the most common types of vasculitis in children. The characteristic clinical manifestations include non-thrombocytopenic purpura, arthritis or arthralgia, abdominal pain, gastrointestinal hemorrhage and renal abnormalities. Thrombosis has been reported as, a rare complication of HSP. We present the case of a 14-year-old boy who was diagnosed with HSP and suspected superior mesenteric vein thrombosis. We reviewed the relevant literature and found eight similar reported cases. HSP is associated with thrombosis and HSP itself and some risk factors may result in thrombosis. We suggest that physicians should monitor patients with HSP who are at a higher risk of developing thrombosis more closely.